Sensation transfer for immersive exoskeleton motor training: Implications of haptics and viewpoints - Ye, Yang; Shi, Yangming; Srinivasan, Divya; Du, Jing (Automation in construction, 2022)
Exoskeletons are promising physical augmentation tools that have shown potential to transform civil engineering operations, but the training is inherently challenging due to the diverse exoskeleton designs, functions, and guidelines across different occupational sectors. Traditional hands-on exoskeleton training is time-consuming and resource-extensive, while virtual training, such as video demonstrations, is ineffective for motor skill learning needed for the exoskeleton. It is unknown if an enhanced virtual environment can facilitate motor skill gaining for exoskeleton training. This paper proposes a haptic-based sensation transfer approach that migrates the egocentric motor experience of an expert exoskeleton user to another novice user, via a passive haptic system in virtual reality. The result of a human-subjects experiment (n = 30) showed that the proposed haptic-based sensation transfer approach significantly improved the motor learning rate in exoskeleton training, and validated the effectiveness of virtual training for even motor-intensive tasks. The proposed haptic-based sensation transfer approach can enrich the embodied motor learning experience and thus can benefit broader applications of motor training at work. It is worth exploring optimal haptic configurations in the future, to enhance embodiment whilst avoiding potential over-reliance on feedback. •This paper presents a new haptic system for immersed exoskeleton training.•A haptic suit with 40 vibrators is programed to transfer feelings of touch from expert to new user.•Human subject experiment (n = 30) was conducted in VR to test the efficacy.•Results show that haptic learning accelerates exoskeleton training with more motion accuracy.•The findings suggest a new motor training method called sensory transfer.